Illness perceptions in cochlear implant users – a longitudinal study - Lehmann, Effi; Heinze-Köhler, Katharina; Glaubitz, Cynthia; Liebscher, Tim; Engler, Max; Hoppe, Ulrich (European Archives of Oto-Rhino-Laryngology, 2024)
Purpose: ‘Illness perceptions’ refers to the thoughts and ideas a person has about an illness. According to Leventhal’s Self-Regulatory Model (SRM), changing the threatening illness perceptions of cochlear implant (CI) recipients can be a further step in optimizing hearing outcomes with the CI. The aims of the present study were to assess users’ illness perceptions and to determine whether perceptions change during six months of CI rehabilitation. Methods: One hundred and thirty-eight participants completed the Brief Illness Perception Questionnaire (Brief IPQ), assessing their illness perceptions on nine scales. Data were collected at a German CI center at first CI fitting and six-month follow-up. After first fitting, participants underwent intensive rehabilitation including auditory training, medical, audiological and psychological treatments. Results: At both assessments, participants tended to view their hearing impairment as a severe threat. On the Brief IPQ, the ‘consequences’ assessment improved during CI rehabilitation, which can be explained by the CI-induced hearing improvement. However, ‘understanding’ and ‘identity’ assessments worsened. This could be because CI recipients only come to realize the full complexity of their hearing impairment during rehabilitation. The other scales and the total score remained unaffected. Conclusions: Current practice in CI rehabilitation seems to be insufficient to improve threatening illness perceptions (except for perceived consequences). This may be because standard information often fails to reach the patients. The development and empirical validation of an intervention program to address individual illness perceptions in CI recipients could be helpful in this context. Further research will be needed to confirm the results.
CRIS-Team Scopus Importer:2024-09-27
Keywords: Brief IPQ; Cochlear implant (CI); Common-sense model of illness representations (CSM); Coping; Hearing impairment; Illness perceptions; Leventhal’s Self-Regulatory Model (SRM)